Knowledge management: BIG DATA as a structuring of information - García Arango, David Alberto; Henao Villa, Federico; Aguirre Mesa, Elkin Darío; Henao Villa, Cesar Felipe; García Arango, David Alberto; Henao Villa, Federico; Aguirre Mesa, Elkin Darío; Henao Villa, Cesar Felipe; García Arango, David Alberto; Henao Villa, Federico; Aguirre Mesa, Elkin Darío; Henao Villa, Cesar Felipe (Corporación universitaria Americana, 2021)
The term Big Data has been used for several years to refer to technologies to describe the acquisition of knowledge obtained through direct experience or perception of the real world. The intention of this research is to explore the role of data analytics as a facilitator of knowledge management. The document supports that text analysis through Big Data and the way it represents one of the most important means to visualize and analyze data, especially data that is not organized in a structured way, have a valuable meaning to optimize the management ofthe knowledge in organizational environments.